(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The techniques of natural ventilation are among the best solutions which serve both to ensure the thermal comfort of the occupants and to reduce the energy bill. In an arid region like southwest of Algeria, which also sees a significant source of wind, the use of wind towers in the design of the building allow us to provide passive cooling. This work aims to evaluate the effect of the natural ventilation of a habitat by a wind tower using a porous media saturated with water and to determine the effect of the tower length on energy efficiency. This objective is possible thanks to the study of the flow by the method of Lattice Boltzmann D2Q9, using a numerical code (LBM - FORTRAN). The results of this work proved that as the length of the tower increases the temperature decreases and the speed increases at the exit of the channel. Also the surface of the porous medium influences the climate at the exit of the tower.